A "Hot, Energized" Benzyne1. Issue 10 (11th January 2013) - Hoffmann, Reinhard W.; Suzuki, Keisuke
<x xml:space="preserve">Abstract</x> Fundamental aspects of chemically activated reactive intermediates can possibly be learned from the novel generation of arynes. The intramolecular [4+2] cycloaddition between a diyne and an (electronically activated) alkyne also provides a new route to generate arynes (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>